Emerging Roles of the Atypical Chemokine Receptor 3 (ACKR3) in Cardiovascular Diseases - Duval, Vincent; Alayrac, Paul; Silvestre, Jean-Sébastien; Levoye, Angélique (Frontiers in Endocrinology, 2022)
Chemokines, and their receptors play a crucial role in the pathophysiology of cardiovascular diseases (CVD). Chemokines classically mediate their effects by binding to G-protein-coupled receptors. The discovery that chemokines can also bind to atypical chemokine receptors (ACKRs) and initiate alternative signaling pathways has changed the paradigm regarding chemokine-related functions. Among these ACKRs, several studies have highlighted the exclusive role of ACKR3, previously known as C-X-C chemokine receptor type 7 (CXCR7), in CVD. Indeed, ACKR3 exert atheroprotective, cardioprotective and anti-thrombotic effects through a wide range of cells including endothelial cells, platelets, inflammatory cells, fibroblasts, vascular smooth muscle cells and cardiomyocytes. ACKR3 functions as a scavenger receptor notably for the pleiotropic chemokine CXCL12, but also as a activator of different pathways such as ß-arrestin-mediated signaling or modulator of CXCR4 signaling through the formation of ACKR3/CXCR4 heterodimers. Hence, a better understanding of the precise roles of ACKR3 may pave the way towards the development of novel and improved therapeutic strategies for CVD. Here, we summarize the structural determinant characteristic of ACKR3, the molecules targeting this receptor and signaling pathways modulated by ACKR3. Finally, we present and discuss recent findings regarding the role of ACKR3 in CVD.